Gastroduodenal intussusception as a rare cause of pancreatitis in a young female Ugandan: A case report - Okello, Michael; Kayondo, Derick; Ocama, Ponsiano (International Journal of Surgery Case Reports, 2021)
acting as the lead point. Gastrointestinal stromal tumors (GISTs) commonly occur in the stomach (40–60%). Other gastric tumors include; adenocarcinomas, leiomyomas, lymphomas among others. When gastric tumors act as lead points in gastroduodenal intussusception, pancreatitis may arise due to compression of the ampulla of Vater or pancreatic head. Gastroduodenal intussusception may mimic other inflammatory upper gastrointestinal conditions leading to delays in early diagnosis and timely intervention. Case presentation: A twenty three year old female with gastroduodenal intussusception secondary to a gastric body GIST with associated pancreatitis. This gastroduodenal mass was initially diagnosed as a pancreatic head echo-complex mass by ultrasound. Confirmatory preoperative diagnosis was made after doing contrasted abdominal computed tomography (CT) scan and upper gastrointestinal endoscopy. Open gastric wedge resection was done. Patient had uneventful recovery and was discharged on the fifth postoperative day. Clinical discussion: Gastroduodenal intussusceptions have non-specific clinical features that may lead to delays in making the correct diagnosis. CT scan is a good imaging modality for diagnosing this condition but access is limited in low resource settings. Resection of the organic cause after reducing the intussusception leads to resolution of the symptoms caused by the intussusception, the GIST and the resultant pancreatitis. Conclusion: Gastroduodenal intussusception is rare and may present with nonspecific clinical features. Pancreatitis may arise due to the compression effects on the ampulla of Vater or pancreatic head. A high index of suspicion is key in making a timely diagnosis.
Keywords: Pancreatitis; Intussusception; Gastrectomy; GIST; Case report; Uganda